EKOWISATA DALAM PERSPEKTIF ETIKA UTILITARIANISME BENTHAM - Eko Sugiarto (Sanjiwani: Jurnal Filsafat, 2023)
This research is a literature research that aims to find out the principles of ecotourism in the perspective of utilitarianism ethics. Data were collected from various literatures on ecotourism and utilitarianism ethics. Data analysis was conducted by comparing the TIES ecotourism principles and Bentham's utilitarianism ethics principles. The conclusion of this research is that ecotourism in the perspective of utilitarianism ethics is seen as something good because the main principles of ecotourism and its derivative principles are in line with the main principles of utilitarianism ethics and the criteria of goodness in the perspective of utilitarianism ethics. The 2nd principle of ecotourism (build environmental and cultural awareness, and respect), the 4th principle of ecotourism (produce direct financial benefits for conservation), and the 8th principle of ecotourism (recognize the rights and spiritual beliefs of the Indigenous People in your community and work in partnership with them to create empowerment) align with Bentham’s first criterion of utilitarianism, namely benefits. The 1st principle of ecotourism (minimize physical, social, behavioral, and psychological impacts) and the 7th principle of ecotourism (design, construct and operate low-impact facilities) align with Bentham’s second criterion of utilitarianism, namely the greatest benefit. Ecotourism’s 3rd principle (provide positive experiences for both visitors and hosts), 5th principle (Generate financial benefits for both local people and private industry), and 6th principle (Deliver memorable interpretative experiences to visitors that help raise sensitivity to host countries’ political, environmental, and social climates) align with Bentham’s third criterion of utilitarianism, which is the greatest benefit to the greatest number of people.